The Housing Market (s) of San Diego - Landvoigt, Tim; Piazzesi, Monika; Schneider, Martin (American Economic Review, 2015)
This paper uses an assignment model to understand the cross section of house prices within a metro area. Movers’ demand for housing is derived from a life-cycle problem with credit market frictions. Equilibrium house prices adjust to assign houses that differ by quality to movers who differ by age, income, and wealth. To quantify the model, we measure distributions of house prices, house qualities, and mover characteristics from micro-data on San Diego County during the 2000s boom. The main result is that cheaper credit for poor households was a major driver of prices, especially at the low end of the market. (JEL D14, D91, R21, R31)